Pengaruh Metode Pembelajaran Mind Mapping Terhadap Minat Belajar Matematika Peserta Didik Pada Materi Perkalian Kelas IV MI Nurul Huda - Kholilatun Najah (Aafiyah: Jurnal Multidisiplin Ilmu, 2023)
One of the problems in education that is very influential is due to a decrease in interest in learning from students. The interest in learning students is very crucial and solutions must be found. Because the interest of students will greatly affect the learning achievement of students. Especially in mathematics, English, and general material that some students have difficulty understanding. This study aims to examine "The Influence of the Mind Mapping Learning Method on the Interest in Learning Mathematics of Students in Class IV Multiplication Material MI Nurul Huda" using quantitative research methods of ordinal data types with a Correlative Associative quantitative approach. The data collection technique that the researchers used was a questionnaire to be filled out by all respondents as many as 30 students, then the results of the questionnaire were inputted to Microsoft Exel and inputted into SPSS 16 to find out whether the data was valid or not and carried out a reliability test. The results showed a significant influence between the Mind Mapping Learning Method on the interest in learning mathematics as evidenced by Approx. Sig. is less than the calculated value of 0.000 < 0.05.